ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERBANKAN: STUDI PADA BANK LAMPUNG KCP NATAR - Adriansyah, Fajar; Fionita, Ita (JURNAL ILMIAH EDUNOMIKA, 2024)
Conventional Commercial Bank credit growth continues to grow, although not as much as growth in third party funds. Credit grew an average of 7.99% per year over the last five years. The objectives to be achieved in this research are: To determine the influence of Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Loan Deposit To Ratio (LDR) and Operational Expenses and Operating Income (BOPO) which have a positive effect on the rate of return on assets in distribution. credit to debtors at PT Bank Lampung KCP Natar. The research method uses multiple linear regression analysis with the Statistical Problem Solution (SPSS) application. Data collection techniques with a financial reporting period of 10 years (2014-2023). The results of this study reveal that financial Ratio performance condition from the Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan Deposit To Ratio (LDR) and Operational Expenses and Operational Income (BOPO) have significant effect to financial performance at PT Bank Lampung KCP Natar. Keywords: Conventional Bank, Credit Distribution, Financial Performance.